The Persistence of Corruption and Regulatory Compliance Failures : Theory and Evidence - Fredriksson, Per (IMF Working Papers; Working Paper ;, 2003)
This paper examines the reasons why corruption and policy distortions tend to exhibit a high degree of persistence in certain regimes. We identify circumstances under which a firm seeks to evade regulations by (1) bribing of local inspectors, and (2) lobbying high-level government politicians to resist legal reforms designed to improve judicial efficiency and eliminate corruption. The analysis predicts that in politically unstable regimes, the institutions necessary to monitor and enforce compliance are weak. In such countries, corruption is more pervasive and the compliance with regulations is low. The empirical results support the predictions of the model.